Omalizumab effectiveness in patients with severe allergic asthma according to blood eosinophil count: the STELLAIR study. Issue 5 (10th May 2018) - Humbert, Marc; Taillé, Camille; Mala, Laurence; Le Gros, Vincent; Just, Jocelyne; Molimard, Mathieu
Omalizumab is a monoclonal anti-IgE antibody used to treat severe allergic asthma (SAA). The aim of the STELLAIR study was to determine the importance of pre-treatment blood eosinophil count as a predictive measure for response to omalizumab. This retrospective real-life study was conducted in France between December 2015 and September 2016 using medical records of SAA omalizumab-treated patients. Response to omalizumab was assessed by three criteria: physician evaluation, reduction of ≥40% in annual exacerbation rate and a combination of both. Response rate was calculated according to blood eosinophil count measured in the year prior to omalizumab initiation. 872 SAA omalizumab-treated patients were included by 78 physicians (723 adults (age ≥18 years) and 149 minors (age 6–17 years)). Blood eosinophil count was ≥300 cells·µL −1 in 52.1% of adults and 73.8% of minors. By physician evaluation, 67.2% of adults and 77.2% of minors were responders and 71.1% adults and 78.5% minors had a ≥40% reduction in the exacerbation rate. In adults, the response rate for combined criteria was 58.4% (95% CI 53.2–63.4%) for blood eosinophils ≥300 cells·µL −1 (n=377) and 58.1% (95% CI 52.7–63.4%) for blood eosinophils <300 cells·µL −1 (n=346). This study shows that a large proportion of patients with SAA have a blood eosinophil count ≥300 cells·µL −1, and suggests that omalizumab effectiveness is similar in "high" and "low" eosinophil subgroups. Omalizumab is a treatment option for severe allergic asthma irrespective of blood eosinophil count http://ow.ly/7tQh30iXNTW